Identification of Sex of Domestic Ruminants by using PCR Technique - Rupali Charjan (Indian Journal of Veterinary Anatomy, 2022)
The aim of this work was to identify the sex of domestic ruminants by using the PCR technique. Six blood samples each from cattle, buffalo, sheep and goat of either sex were collected. The DNA extraction was conducted by using a DNAextraction kit. Extracted DNAwas subjected to PCR using the sex-determining region of the Y chromosome gene (SRY) as a biological marker. The PCR amplicon was loaded in 2% agarose gel and was run under a submersible electrophoresis machine. The band patterns were observed under U.V. Transilluminator. The banding pattern showed fragments at 122bp in all males, but no fragments were observed in females in all the species under study.